A Metabolomics-Based Approach for Diagnosing NAFLD and Identifying Its Pre-Condition Along the Potential Disease Spectrum - Masanori Nojima; Takeshi Kimura; Yutaka Aoki; Hirotaka Fujimoto; Kuniyoshi Hayashi; Junya Ohtake; Mariko Kimura-Asami; Kazuhiko Suzuki; Kevin Urayama; Masaaki Matsuura; Taka-Aki Sato; Katsunori Masuda (Livers)
Introduction: The significant impact of nonalcoholic fatty liver disease (NAFLD) on public health, combined with the limitations of current diagnostic approaches, demands a more comprehensive and accurate method to identify NAFLD cases in large general populations. Methods: In this cross-sectional study, we recruited 3733 individuals (average age 51.8 years) who underwent health check-ups between October 2015 and October 2016. NAFLD was diagnosed using ultrasound; 114 serum metabolites were measured using gas chromatography–mass spectrometry. We adopted the least absolute shrinkage and selection operator (LASSO) method to build a metabolomic-based diagnostic model. Results: NAFLD was diagnosed in 826 participants. While each metabolite exhibited a limited diagnostic ability for NAFLD when used individually, compared with BMI, the model constructed using the LASSO demonstrated adequate diagnostic power (area under the curve [AUC] 0.866, 95% confidence interval 0.847–0.885 in test set) and even for lean (BMI < 23) populations (AUC for LASSO 0.828, for BMI 0.78). Moreover, the LASSO model-derived ‘pre-NAFLD’ condition showed a potential association with insulin resistance and elevated triglycerides. Conclusions: Our metabolomic-based approach provides a comprehensive evaluation of NAFLD or ‘pre-NAFLD’, both considered parts of a hypothetical ‘NAFLD spectrum’, independent of body type. Metabolomics could offer additional diagnostic benefits and potentially expand the disease concept.